Pengembangan Adaptive Flipbook Pengoperasian Adobe Photoshop CS 6 bagi Tunarungu untuk Meningkatkan Keterampilan Editing di Sekolah - Syahidan, Hanif; Iswari, Mega (Jurnal Penelitian Pendidikan Khusus, 2024)
This research is motivated by the problem faced by deaf children who wish to learn editing skills using Photoshop. Existing learning media such as books, e-books, and YouTube tutorials are not adapted to the needs of deaf children. Therefore, the researcher developed an Adaptive Flipbook for Operating Adobe Photoshop CS6 to facilitate learning editing skills for deaf children. The method used is Research and Development (R&D), which includes five stages: research and information, planning, developing a preliminary form of a product, preliminary field testing, and main product revision. Validation was conducted by three experts: a design expert, an education expert, and a technology expert. The validation results from the three experts showed an average score of 2.4, classified as very valid. Suggestions and comments from the experts were used to revise the product. The validation results indicate that this flipbook can be an effective learning medium for deaf children to learn editing using Adobe Photoshop CS6.